C: how to program - Deitel, Paul J.; Deitel, Harvey M., 1945- (Englewood Cliffs, N.J. : Prentice Hall, 1994)
Highly practical in approach, it introduces fundamental notions of structured programming, gets up to speed quickly, and covers not only the full C language, but includes a review of library functions and a solid introduction C++ and object-oriented programming. Emphasizes the principles of structured programming and software engineering; includes tips on common programming errors, good programming practices, portability, performance, and software engineering; demonstrates, incrementally, the features of C within the context of properly structured and well documented, complete working C programs and sample executions; uses ANSI C throughout; offers an introduction C++ and object-oriented programming.
Includes bibliographical references and index.
Keywords: C (Computer program language); C++ (Computer program language); Computing